Targeting long non-coding RNA RP11-502I4.3 inhibits the trend of angiogenesis in diabetic retinopathy - Lan Zeng; Yuhao Wu; Lijuan Zhu; Junhao He; Yuan Yuan; Xiaocong Wang; Kai Tang; Wei Tan (PLoS ONE, 2025)
Diabetic retinopathy (DR) is a leading cause of blindness. We hypothesised that the long non-coding RNA RP11-502I4.3 may be involved in angiogenesis associated with DR. We investigated the role of RP11-502I4.3 in DR by examining its regulation of vascular endothelial growth factor (VEGF). We assessed differences in RP11-502I4.3 expression between the control group and streptozotocin-induced diabetic rats or high glucose (HG)-stimulated human retinal microvascular endothelial cells (HRMECs). VEGF expression was measured with and without lentiviral vectors overexpressing RP11-502I4.3. We analysed the structural alterations related to DR after overexpressing RP11-502I4.3. Our analysis revealed that RP11-502I4.3 expression was lower in the retinas of diabetic rats and HG-stimulated HRMECs compared with normal glucose conditions. Overexpressing of RP11-502I4.3 resulted in decreased VEGF levels. Diabetic rats exhibited retinopathy characterised by thinning of the retinal layer thickness, structural changes in the inner and outer nuclear layers, a reduced count of retinal ganglion cells, and the presence of acellular capillaries. The proliferative activity, migration count, and tube formation ability of HG-treated HRMECs were significantly higher than those of the control group. However, these changes were inhibited by RP11-502I4.3 overexpression. Overexpression RP11-502I4.3 might inhibit retinopathy of diabetic rats and HG-induced angiogenesis by downregulating VEGF expression.